ECONOMIC MODERNIZATION IN THE INDONESIA–MALAYSIA BORDERLANDS: FROM INFORMAL BARTER SYSTEMS TO A DIGITAL TRADE ECOSYSTEM - Sigit Sugiardi (CV. ADIBA AISHA AMIRA, 2026)
This study aims to analyze the economic modernization of the Indonesia–Malaysia borderlands by transforming informal barter systems into integrated digital trade ecosystems. The research focuses on understanding how technological development, regional integration, and institutional change reshape cross-border economic activities in frontier communities. This study employs a qualitative approach using the library research method by analyzing secondary data from Scopus-indexed journal articles, books, policy reports, and official publications published between 2020 and 2025. The data were examined using descriptive-analytical and thematic analysis techniques to identify patterns of border economic transformation, digitalization trends, and challenges of regional economic integration. The findings reveal that border economies in the Indonesia–Malaysia frontier are experiencing a gradual transition from traditional barter-based trade toward digitalized commercial systems supported by fintech, mobile payments, e-commerce, and logistics integration. However, the transformation remains uneven due to disparities in digital infrastructure, technological literacy, and institutional capacity. Informal trade systems persist because they provide flexibility, social trust, and economic access for local communities. The study also finds that digitalization contributes positively to financial inclusion and market expansion but simultaneously creates digital inequality between urbanized and remote border regions. This study contributes theoretically by integrating Border Economic Transformation Theory, Digital Ecosystem Theory, and Regional Integration Theory to explain the coexistence of traditional and modern economic systems in borderlands. Practically, the research highlights the importance of inclusive border development policies that combine technological modernization with community empowerment and socioeconomic sustainability. The study concludes that sustainable border economic modernization requires adaptive governance, equitable digital access, and participatory regional integration strategies.